Settlement of Criminal Cases through Integration Customary Law Values Angkon Muakhi in Lampung Province - Hasan, Zainudin; Dewi, Erna; Fardiansyah, Ahmad Irzal; Setiawan, Refly; Abdurrahman, Abdurrahman (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
The current Indonesian criminal law, although it has used the restorative justice method, has not been able to resolve the core of the problem and has not restored balance in society, so the settlement of criminal acts is not complete to the community, the victim and the victim's family. The importance of criminal law policies for the settlement of criminal cases through the integration of Angkon Muakhi law is to realise justice, benefit, balance, and kinship in criminal law enforcement. This research method uses the combined theory paradigm and mixed legal system to generate new ideas in settling criminal cases. This research is normative juridical and empirical juridical research with a socio-legal approach. In-depth interviews were carried out in primary data collection; sources were determined by the snowball method, while secondary data collection was carried out using a literature study. The findings of this study indicate that the enforcement of criminal law at this time still does not involve the community. There are still the rights of victims' families and communities that have not been restored; even though restorative justice has been resolved, it still leaves disputes, seeds of conflict and grudges both from the victim, the victim's family and the surrounding community. Prison sentences are still prioritised in light cases and negligence, both in the investigation process, prosecutors' demands, and the judge's decision. The importance of resolving criminal cases through integrating the customary law values of Angkon Muakhi, which can resolve cases, conflicts, hostilities and disputes between perpetrators, victims and the community.